ANALISIS MISKONSEPSI GERAK MELINGKAR PADA BUKU SEKOLAH ELEKTRONIK (BSE) FISIKA SMA KELAS X SEMESTER I - Fitrianingrum, Nurul; Sunarno, Widha; Harjunowibowo, Dewanto (Jurnal Pendidikan Fisika, 2013)
The research has purpose to investigate the books of physics, such as (1) the existance of misconseptions, (2) the percentage of misconceptions, and (3) other identification of aspects which has potential to cause misconception in circular motion particularly. These books are: (a) Tri Widodo, Fisika untuk SMA dan MA Kelas X, (b) Dudi Indrajit, Mudah dan Aktif Belajar Fisika untuk Kelas X Sekolah Menengah Atas/Madrasah Aliyah, and (c) Setya Nurachmandani, Fisika 1 untuk SMA/MA Kelas X first edition 2009 published by Pusat Perbukuan Kemendikbud. The research is a descriptive qualitative research. The object of this research is the circular motionâs concepts. The techniques of data collection in this research were done by literature and interview the expertise to get the true concept. The techniques of data validation was persistence or constancy of observation. Data analysis technique that is used in this research is a qualitative descriptive analysis consist of four stages; data collection, data reduction, data display, and conclusions drawing and verifying. Based on data analysis it can be concluded that: (1) there are no misconceptions, (2) the percentage of misconceptions are 0%, and (3) other descriptions identification are: correct concept, the concept does not exist, the picture correction, writing notation correction, writing unit corrections, writing formulation correction, writing result calculation correction, and correction for writing explanation formula in correction the concept of circular motion in the three electronic books. Keyword: misconception, physics elektronic books, circular motion.